On Jordan's Banks : Emancipation and Its Aftermath in the Ohio River Valley - Bigham, Darrel E. (Book collections on Project MUSE., 2006)
The story of the Ohio River and its settlements are an integral part of American history, particularly during the country's westward expansion. Bigham examines the lives of African Americans in the counties along the northern and southern banks of the Ohio river both before and in the years directly following the Civil War.